How do aesthetics drive customer retention in Bali cafes? - Shu, Efin; Tisna, Annarica (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
In today’s competitive food service industry, aesthetics are key to customer retention. The food service landscape is changing as customers want to fulfill more than just their hunger and thirst. Customers now care more about the looks of the place and food to satisfy their hedonistic desire. This research aims to determine the influence of aesthetic attributes on customer retention through customer satisfaction in café businesses in Bali. This research uses the quantitative method, with the data analyzed using the SmartPLS 4 statistical software. Data is collected with Google Forms using a convenience sampling technique. The results show that food aesthetics showed a significant path coefficient of 0.035 with p<0.05 on customer satisfaction. Labor aesthetics showed a significant path coefficient of 0.000 with p<0.05 on customer satisfaction. Customer satisfaction showed a significant path coefficient of 0.000 with p<0.05 on customer retention. Food and labor aesthetics significantly affected customer retention through customer satisfaction with a path coefficient of 0.046<0.05 for food aesthetics and 0.000<0.05 for labor aesthetics. However, the physical environment aesthetics do not significantly influence customer satisfaction with a path coefficient of 0.376>0.05 and do not significantly influence customer retention through customer satisfaction with a path coefficient of 0.374>0.05. Therefore, the management of the café in Bali should not rely solely on the physical environment aesthetics, instead, they should maintain the food and labor aesthetic. They should also enhance customer satisfaction through the three aesthetic attributes as it will lead to customer retention.